2007
DOI: 10.1038/sj.emboj.7601561
|View full text |Cite
|
Sign up to set email alerts
|

Full-length p40phox structure suggests a basis for regulation mechanism of its membrane binding

Abstract: The superoxide-producing phagocyte NADPH oxidase is activated during phagocytosis to destroy ingested microbes. The adaptor protein p40phox associates via the PB1 domain with the essential oxidase activator p67phox, and is considered to function by recruiting p67phox to phagosomes; in this process, the PX domain of p40phox binds to phosphatidylinositol 3-phosphate [PtdIns(3)P], a lipid abundant in the phagosomal membrane. Here we show that the PtdIns(3)P-binding activity of p40phox is normally inhibited by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 52 publications
(105 reference statements)
1
59
1
Order By: Relevance
“…1A, center), as reported previously in RAW 264.7 macrophages (12) and PBL-985 granulocytes (28). We (12,27) and others (13,31) (Fig. 1B).…”
Section: H 2 O 2 Induces Conformational Changes and Targeting Of P40 supporting
confidence: 63%
See 2 more Smart Citations
“…1A, center), as reported previously in RAW 264.7 macrophages (12) and PBL-985 granulocytes (28). We (12,27) and others (13,31) (Fig. 1B).…”
Section: H 2 O 2 Induces Conformational Changes and Targeting Of P40 supporting
confidence: 63%
“…Cho and Stahelin (58) described a general mechanism of membrane-protein interactions in which membrane adsorption of PX domain-containing proteins such as p47 phox and p40 phox (18,56) is initially driven by nonspecific electrostatic interactions (between anionic lipids in membranes and cationic surfaces of proteins) and by diffusion, which is then followed by specific interaction with PIs and interfacial penetration (66) of hydrophobic and aromatic residues located near its respective binding site of PIs. Crystallographic studies on p40 phox , revealed that intramolecular PX-PB1 domain interactions are sterically inhibiting access of the PX domain with membraneembedded PI(3)P, rather than completely masking the PI(3)Pbinding site (13); in other words, the PX domain is able to access PI(3)P in certain conditions because three-dimensional positioning of membrane-embedded PI(3)P changes during phagosome formation. This speculation is supported by reports that full-length p40 phox binds to soluble PI(3)P to the same extent as the PX domain (39) and that full-length p40 phox binds to PI(3)P in surface plasmon resonance and lipid monolayer assays in which PI(3)P is flexible in the lipid monolayer (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p40 phox contains an N-terminal PtdIns(3)P-binding PX domain (19,20), a central SH3 domain capable of interacting with a proline-rich region in p47 phox in vitro (21,22), and a C-terminal PB1 domain that is required for constitutive interaction with p67 phox (23). Recently, the structure of full-length p40 phox was solved (24). The structure, together with a companion cell biology-based study, showed that p40 phox exists in a "closed" state where the PX and PB1 domains interact with each other, preventing the PX domain from interacting with PtdIns(3)P-containing membranes (25).…”
mentioning
confidence: 99%
“…The N-terminal region of p67phox interacts with GTP-bound Rac and the activation domain of p67phox allows electron flow in the p22phox/Nox2 complex required for superoxide production [56,133]. The fully active NADPH oxidase is also under complex regulation by lipid metabolites that interact with the Phoxhomology (PX) domains of p47phox and p40phox [2,67].…”
Section: Regulation Of Nadph Oxidasementioning
confidence: 99%